Flow of Non-Newtonian Fluid in Curved Duct with Varying Aspect Ratio - M., Hadi; A., Fathi; A., Zainy (Iraqi Journal of Science, 2025)
In this study consideration is given to viscous, incompressible, second order fluid flowing in a rectangular duct, with varying aspect ratio, under the action of the pressure gradient. In particular consideration is given to visco-inelastic liquid. An orthogonal coordinates system has been framed to describe the fluid motion and it is found that the motion equations are controiled by two parameters namely: Dean number and the Non-Newtonian parameter. Soluuons for the secondary flow and the axial velocity are derived as perturbations over straight pipe appearing through the dean number. The finite-difference method is employed to find a perturbation solution. These solutions have heen developed in certain coordinates for harmonic and biharmonic equations. This study ended with the effect of the non-dimensional and aspect ratio parameters mentioned above on the secondary motion